2020
DOI: 10.1002/anie.202004008
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐Induced Pro‐Protein Therapy Assisted by a Self‐Catalyzed Nanozymogen

Abstract: The success of intracellular protein therapy demands efficient delivery and selective protein activity in diseased cells. Therefore, a cascaded nanozymogen consisting of a hypoxia‐activatable pro‐protein, a hypoxia‐inducing protein, and a hypoxia‐strengthened intracellular protein delivery nanovehicle was developed. RPAB, an enzymatically inactive pro‐protein of RNase, reversibly caged with hypoxia‐cleavable azobenzene, was delivered with glucose oxidase (GOx) using hypoxia‐responsive nanocomplexes (NCs) consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…An alternative approach involves the covalent modification of proteins with anionic species, such as carboxylic acid, [ 11 ] boronic acid, [ 12 ] or other anionic proteins, [ 5 ] peptides, [ 13 ] nucleic acids, [ 14 ] and polymers, [ 2 ] such that the modified proteins could form nanocomplexes (NCs) with cationic materials via electrostatic interactions. Although these chemically modified moieties could be removed by intracellular stimuli such as reduction, [ 15 ] reactive oxygen species (ROS), [ 12 ] enzyme, [ 16 ] hypoxia, [ 17 ] and endo/lysosomal acidity, [ 18 ] the bioactivity of the native protein is often compromised. In addition, the complicated synthetic procedures may impede the potential translation.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach involves the covalent modification of proteins with anionic species, such as carboxylic acid, [ 11 ] boronic acid, [ 12 ] or other anionic proteins, [ 5 ] peptides, [ 13 ] nucleic acids, [ 14 ] and polymers, [ 2 ] such that the modified proteins could form nanocomplexes (NCs) with cationic materials via electrostatic interactions. Although these chemically modified moieties could be removed by intracellular stimuli such as reduction, [ 15 ] reactive oxygen species (ROS), [ 12 ] enzyme, [ 16 ] hypoxia, [ 17 ] and endo/lysosomal acidity, [ 18 ] the bioactivity of the native protein is often compromised. In addition, the complicated synthetic procedures may impede the potential translation.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 10c, GOx is an enzyme that effectively catalyzes the conversion of glucose, oxygen, and water into H 2 O 2 and gluconic acid. Very recently, Yin and co‐workers [ 99 ] designed a hypoxia triggered cascade, self‐catalyzed nanozymogen, to deliver hypoxia‐strengthened RPAB (a proprotein of Rnase A reversibly caged with hypoxia‐cleavable azobenzene) and GOx. Upon the consumption of oxygen by GOx, the tumor hypoxia may be exacerbated to trigger the decomposition of AOEI to further release GOx and recover RPAB to active RNase.…”
Section: Hypoxia‐responsive Strategiesmentioning
confidence: 99%
“…24,25 For example, Chen and co-workers 26 amplified prodrug activation by sequentially delivering combretastatin A4 to upregulate metalloproteinase 9 (MMP9) and MMP9-activated doxorubicin (DOX) prodrug and promote activation of tumor-selective prodrug for cancer therapy. In addition, Yin and co-workers 27 reported that a pro-protein therapy was activated by self-amplified hypoxia associate enzymes. Consequently, development of an enzyme-responsive prodrug, which can simultaneously retain selectivity of enzymeresponsive for tumor targeting and amplification of the enzyme response signal for enhanced therapeutic efficiency, remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%